Bringing economic complexity to the intra-urban scale: The role of services in the urban economy of Belo Horizonte, Brazil. (January 2023) - Magalhães, Lucas; Kuffer, Monika; Schwarz, Nina; Haddad, Mônica
Abstract: This study explores the formation of economic complexity within a city from the Global South, during 2011–2019. It proposes an expanded interpretation of the Economic Complexity Index (ECI) to be applied at the intra-urban context of Belo Horizonte, Brazil, focusing on three different spatial levels of analysis (i.e., local, neighbourhood, and community levels). By applying the index to these three levels, instead of regional or national administrative boundaries commonly used in literature, this study contributes to approximating the observation of economic complexity to the actual geographical scales at which economic interactions take place, allowing for intra-urban comparisons. The proposed ECI includes the service economy, amenities, and retail, in addition to commonly observed manufacturing industry. Methodologically, this case study introduces the Urban Economy Space network diagram to the expanded ECI as an effort to holistically consider all economic sectors happening in a city. The main findings are twofold. First, the city services classified as more complex by the ECI are aligned with the theory of post-industrial economic activities: financial, telecommunications, scientific and technical services, etc. Second, government-led institutions such as healthcare facilities, higher education institutions, etc., appear on the top tier of economic complexity, indicating that local and national governments can contribute to complexifying local economies. Highlights: Focus on observing the economic structure of a city from the Global South, with the lens of the Economic Complexity literature. The Economic Complexity Index is successfully transferred to intra-urban areas, as an extension to regional or national levels. The Economic Complexity Index is successfully applied to the service sector, as an addition to manufacturing and amenity industries. Local and national governments have a decisive role in complexifying local economies, as public-run institutions were considered highly complex. The Urban Economy Space allows the reading of a city's composition of economic activities, identifying paths for complexification.